Low-phosphorus diets during late-finishing decrease cost of gain with minimal effect on growth performance, carcass characteristics, and meat quality - I Mavromichalis; I H Kim; L L Burnham; M M Rantanen; Robert H Hines; Joe D Hancock; Donald H Kropf; Keith C Behnke (Kansas Agricultural Experiment Station Research Reports, 1995)
Partially omitting (up to 66 %) the supplemental inorganic phosphorus (P) source from a late-finishing (190 to 250 lb) diet resulted in slightly greater ADG and backfat thickness, which probably resulted from the greater feed (energy) intake. Meat quality was unaffected by treatment. Thus, during late-finishing, a total P concentration of .40% can be used to decrease diet cost without decreasing performance or meat quality of high-lean pigs.; Swine Day, Manhattan, KS, November 16, 1995
Keywords: Swine day; 1995; Kansas Agricultural Experiment Station contribution; no. 96-140-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 746; Swine; Phosphorus; Performance; Carcass; Meat